Enhanced heat transfer performance in channel with delta-wing perforated V-type baffles - Eiamsa-ard, Smith; Phila, Arnut; Thianpong, Chinaruk; Chuwattanakul, Varesa; Maruyama, Naoki; Hirota, Masafumi (My University, 2023)
The article examines the influence of delta-wing V-type baffles (DW-PVBs) on the average Nusselt number, local Nusselt number distribution, pressure losses, and thermal performance behaviors in a channel. Delta-wing perforated V-type baffles (DW-PVBs) mounted in a regular manner on the bottom of a channel produced two pairs of longitudinal counter-rotating vortices to enhance chaotic fluid mixing and destabilize the boundary layer, hence boosting the heat transfer. The geometric characteristics of the delta-wing V-type baffle (DW-PVBs) located on the bottom of the channel were examined at relative baffle blockage and pitch ratios (BR = h/H = 0.3 and p/H = 1.5), and five delta-wing attack angles, θ = 0o (solid V-shaped baffle), 22.5°, 45°, 67.5°, and 90°. The present DW-PVBs mounted on the channel were designed to mitigate pressure loss due to flow blockage. The experiment was done by permitting air to flow through a channel at Reynolds numbers (Re) ranging from 6000 to 24,000. The present results show that the friction factor using the DW-PVBs decreased considerably with increasing θ values. The experimental results revealed that small θ values yielded greater heat transfer and resistance than large θ values. The DW-PVBs with θ = 22.5° performed better than inserts with other θ values in terms of heat transfer rate. It was also observed that the DW-PVBs with θ = 45° gave the maximum thermal performance factor (TPF), while presenting a 13.64–17.26% lower friction factor than the solid V-shaped baffle. Furthermore, it was also found that the DW-PVBs with θ = 0°, 22.5°, 45°, 67.5°, and 90° gave peak TPF values of up to 1.87, 1.89, 1.91, 1.87, and 1.84 at the lowest Reynolds number, 6000.
Keywords: Delta-wing; Heat transfer; Heat transfer enhancement; Turbulent flow; V-type baffle